2014
DOI: 10.1016/j.jtbi.2014.02.028
|View full text |Cite
|
Sign up to set email alerts
|

A mathematical model for pancreatic cancer growth and treatments

Abstract: Pancreatic cancer is one of the most deadly types of cancer and has extremely poor prognosis. This malignancy typically induces only limited cellular immune responses, the magnitude of which can increase with the number of encountered cancer cells. On the other hand, pancreatic cancer is highly effective at evading immune responses by inducing polarization of pro-inflammatory M1 macrophages into anti-inflammatory M2 macrophages, and promoting expansion of myeloid derived suppressor cells, which block the killi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(62 citation statements)
references
References 45 publications
0
62
0
Order By: Relevance
“…Data from this study may also be used to support development of advanced mathematical models that simulate cytokine interactions on cells within the pancreas microenvironment. Similar theoretical studies have been conducted by our group for pancreatic cancer and are currently underway as an extension into CP 48 . Finally, these data may also aid efforts in implementing new diagnostic or prognostic strategies in CP.…”
Section: Discussionmentioning
confidence: 67%
“…Data from this study may also be used to support development of advanced mathematical models that simulate cytokine interactions on cells within the pancreas microenvironment. Similar theoretical studies have been conducted by our group for pancreatic cancer and are currently underway as an extension into CP 48 . Finally, these data may also aid efforts in implementing new diagnostic or prognostic strategies in CP.…”
Section: Discussionmentioning
confidence: 67%
“…But they did not investigate the role of the innate partners of Treg, such as alternatively activated macrophages and MDSCs, and their corresponding interactions with other cell types. Conversely, Louzoun et al [39] considered the interconversion between classically activated macrophages (M 1 -like, immune-promoting) and alternatively activated macrophages (M 2 -like, cancer-promoting), but did not consider the role of adaptive partners of M 2 such as Treg. They showed that the enhancement of M 1 to M 2 conversion by factors secreted by cancer cells and/ or cancer-associated fibroblasts and the positive feedback between cancer cells and CAFs are essential to give rise to a bistable switch from an immune-promoting (cancer-killing) state to an immune-modulating/suppressing (cancer-promoting) state as the cancer-killing rate of CD8 + cells decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, cancer is an evolutive and very heterogeneous disease with many different stages involving temporal variability on the tumour dynamic and on the patient state that cannot be easily predicted. This requires the development of pathophysiological models that integrate the underlying key mechanisms precisely describing the evolution of the disease for predicting and understanding its behaviour and its response to treatment [1014]. …”
Section: Introductionmentioning
confidence: 99%